2018
DOI: 10.1021/acsmacrolett.8b00888
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Hydrogel-Nanostructure Hybrids as Robust Biofilm-Resistant Polymeric Materials

Abstract: Despite extensive efforts toward developing antibiofilm materials, efficient prevention of biofilm formation remains challenging. Approaches based on a single strategy using either bactericidal material, antifouling coatings, or nanopatterning have shown limited performance in the prevention of biofilm formation. This study presents a hybrid strategy based on a lipid-hydrogel-nanotopography hybrid for the development of a highly efficient and durable biofilm-resistant material. The hybrid material consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…S7A, i to iv). Previous studies reported that nanostructures with sharp tips can induce lysis of bacterial cells while physically rupturing the cell membrane ( 6 , 39 ). Thus, they are effective for the prevention of biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S7A, i to iv). Previous studies reported that nanostructures with sharp tips can induce lysis of bacterial cells while physically rupturing the cell membrane ( 6 , 39 ). Thus, they are effective for the prevention of biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they are effective for the prevention of biofilm formation. MPC is a well-known effective antifouling material ( 4 , 39 ). By generating a nanoscale needle array or coating of the antifouling polymer MPC over the skin layer, the biofilm resistance of the dynamic composite can be further enhanced for the same T and H values (fig.…”
Section: Resultsmentioning
confidence: 99%
“…UVNIL is able to produce high-quality features that can be used in biofilm [ 129 ], vascular muscle cell function [ 99 ], cell stimulation [ 98 ], data storage [ 136 ], as well as in fluidic [ 137 ] applications. Periodic patterns that can be obtained by employing UVNIL are various ( Table 2 ) and include arrays of grooves made of inorganic–organic polymer [ 137 ], of poly(urethane acrylate) (PUA) [ 99 ], and of poly(ethylene glycol) (PEG)-based hydrogel grooves [ 98 ].…”
Section: Top–down Lithographic Methodologiesmentioning
confidence: 99%
“…Periodic patterns that can be obtained by employing UVNIL are various ( Table 2 ) and include arrays of grooves made of inorganic–organic polymer [ 137 ], of poly(urethane acrylate) (PUA) [ 99 ], and of poly(ethylene glycol) (PEG)-based hydrogel grooves [ 98 ]. Other relief patterns are represented by arrays of 2-methacryloyloxyethyl phosphorylcholine (MPC) grafted poly(ethylene glycol) dimethacrylate (PEGDMA) nanoneedles of a periodicity of few hundreds nanometers [ 129 ] ( Figure 6 e), arrays of metallopolymer nanodots and nanolines [ 136 ], or even arrays of poly(β-hydroxyl thio-ether) microlines, microstars ( Figure 6 f), microgrids, cylindrical cavities, and other micropatterns with acute angles [ 130 ]. Again, repetitive UVNIL combined with the use of two molds comprised of patterns of different dimensions can lead to a variety of hierarchical micro–nano recessed patterned polymer structures of high aspect ratio [ 138 ].…”
Section: Top–down Lithographic Methodologiesmentioning
confidence: 99%
“…Another interesting type of antibacterial surfaces is those that physically destroy bacterial cell walls through the use of sharp, needle‐like nanoscale structures oriented normally to the substrate surface (Ivanova et al., 2012, 2013; Mohammadi Nafchi et al., 2014; Park et al., 2019; Podporska‐Carroll et al., 2015; Tan et al., 2020; Tripathy et al., 2017; Tsui et al., 2018). When bacterial cells adsorb onto surfaces with such sharp nanoscale features, the features perforate the bacterial cell walls.…”
Section: Other Antifouling Surface Modificationsmentioning
confidence: 99%